A New Practical Surgical Technique for Hymenoplasty: Primary Repair of Hymen With Vestibulo-Introital Tightening Technique. (31st March 2020) - Eserdağ, Suleyman; Kurban, Didem; Kiseli, Mine; Alan, Yasemin; Alan, Murat
Abstract: Background: Hymenoplasty is distinct from other genital surgeries with its ethical and psychological issues. It is performed to narrow the vaginal opening to ensure vaginal bleeding with penetration. There are various kinds of techniques with different success rates. Objectives: The authors sought to report a new hymenal reconstruction technique with vestibulo-introital tightening with the results of 145 procedures. Methods: The new technique included a diamond-shaped incision to the vestibulum with the base in the posterior midline and superior corner 2 to 3 cm higher above the hymen. The angles were accommodated according to the degree of tightening, and the submucosal layer was closed from the apex downwards involving the vaginal mucosa. Results: The satisfaction rate of the patients was 99.3%. No adverse events were observed. Conclusions: Compared with previous techniques described, this hymenal reconstruction technique is an alternative with the advantage of low risk of loosening because the tension on the hymen alone is decreased. Additional tightening of the introitus increases the satisfaction rates in some patients. Level of Evidence: 4: